ESG reporting divergence - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2023)
In this paper, we provide the first large-sample empirical analysis of the consequences of ESG reporting divergence among U.S. firms. We construct and validate an ESG reporting divergence measure based on the dissimilarities in ESG reporting across firms. Validation tests confirm that it is lower for firm-pairs using the same ESG reporting framework, with similar size, and with similar ESG performance than for other firm-pairs. We find that ESG reporting divergence is positively associated with ESG rating disagreement and weakens the positive association between ESG ratings and ESG fund allocation. These results indicate that ESG reporting divergence reduces the usefulness of ESG reporting for ESG rating providers and ESG fund managers. We corroborate our findings using a sample of U.S. firms that are likely affected by the EU’s ESG reporting regulation.